Sport branding insights - Stavros, Constantino; Smith, Aaron 1972- (Sport business insights, 2020)
"In a sporting world dominated by media and money, an understanding of sport branding is an essential skill for any sport manager. Success means being able to 'brand'-and therefore differentiate-a sport club, player, code or event in a highly competitive entertainment market. For anyone seeking to understand or manage sport, this book offers an immediate and salient insight into the complex and dynamic process of creating a powerful sport brand. The book explains how a sport brand goes beyond just an identifying badge, reinforced by a name or a logo that helps sport consumers recognise a product or an organisation. It reveals how a brand becomes linked with consumers' opinions and perceptions of a sport product and the organisation that owns it. Readers will learn how to create a powerful brand that has both recognition in the market and strong associated imagery, by imbuing it with a spirit of the past through appeals to tradition, by endowing it with human qualities of emotionality, thought and volition, and through the use of characters, colours, texts and symbols. It also provides a brief guide to the new domains of digital sport branding and social media. Concise, informative and entertaining, this is an essential resource for anyone exploring or practicing the business of sport"-- Provided by publisher